Effect of shear flow on the hydrodynamic drag force of a spherical particle near a wall evaluated using optical tweezers and microfluidics. Issue 34 (10th August 2021) - Geonzon, Lester C.; Kobayashi, Motoyoshi; Adachi, Yasuhisa
Abstract : The hydrodynamic drag force on a spherical particle in shear flow near-wall is investigated using optical tweezers and microfluidics. Abstract : The hydrodynamic drag force on a spherical particle in shear flow near-wall is investigated using optical tweezers and microfluidics. Simple shear flow is applied using a microfluidic channel at different volumetric flow rates. The hydrodynamic drag force exerted on the particle is detected from the displacement of the trapped particle. The effect of the wall is obtained from the force balance of the trapping and hydrodynamic drag force employing the exact solution of the theoretical model using the lubrication theory for a sphere near the wall. Here, we report the experimentally obtained hydrodynamic drag force coefficient under the influence of shear flow. The drag correction factor increases with decreasing distance from the wall due to the effect of the wall surface. We found that the calculated hydrodynamic drag force coefficient is in quantitative comparison with the theoretical prediction for a shear flow past a sphere near-wall. This study provides a straightforward investigation of the effect of the shear flow on the hydrodynamic drag force coefficient on a particle near the wall. Furthermore, these pieces of information can be used in various applications, particularly in optimizing microfluidic designs for mixing and separations of particles or exploiting the formation of the concentration gradient of particles perpendicular to flow directions caused by the non-linear hydrodynamic interactions.